Skeletally anchored mesialization of molars using digitized casts and two surface-matching approaches: Analysis of treatment effects - Becker, Kathrin; Wilmes, Benedict; Grandjean, Chantal; Vasudavan, Sivabalan; Drescher, Dieter (Journal of orofacial orthopedics, 2018)
Purpose To (1) quantify the three-dimensional treatment effect of a Mesialslider appliance using superimposed digital models, (2) to evaluate anchorage loss (measured by incisor displacement), and (3) to assess agreement between two different matching approaches, i.e., control point (CP)-based and iterative closest point (ICP) matching. Methods In a retrospective study, the effects of a skeletally anchored uni- and bilateral mesialization appliance (Mesialslider) as well as simultaneous mesialization and distalization appliance (Mesio-Distalslider) were evaluated in 48 subjects (aged 11–53 years). Pre- and posttreatment casts were digitized and superimposed with two different approaches, i.e., using ten manually selected control points located at the anterior palate and by means of an automated ICP-matching approach using a standardized palatal reference area. The treatment effects were evaluated using control points on the maxillary central incisors and maxillary molar teeth, and the methods were compared through the application of linear regression analyses and computation of alignment errors. Results Average upper molar mesialization was 6.3 ± 2.6 mm. Anchorage loss, designated as the mean amount of upper incisor displacement, was less than 0.5 mm in all dimensions investigated. Using the measurement method sufficient registration was possible using both approaches and corresponding tooth movements were significantly correlated ( p < 0.01). Conclusions Accurate measurements of tooth displacement can be performed using both CP- and ICP-based matching approaches. Within the limits of performing a retrospective study, a premolar width of molar mesialization appeared possible without clinically relevant anchorage loss.